Micro-entrepreneurship, Institutional Environment and the COVID-19 Pandemic: A Comparison of Weaving Clusters in West Bengal, India - Indranil De; Saswata Narayan Biswas
This article compares micro-enterprises$1 (Bperformance and the entrepreneurial ability of weavers as perceived by the weavers themselves under two different institutional environments: one dominated by a cooperative society and the other dominated by private traders. Weavers in the private trader-dominated institutional environment are more likely to introduce new designs, develop new products and usher client satisfaction. However, the determinants of overall entrepreneurial ability reveal that after controlling for several factors, the weavers associated with a cooperative society seem to have significantly higher abilities. Analyzing the marginal effects of the institutional environment, it is observed that the perceived quality of handlooms, weaver$1 (Bs ability to bargain for returns and ability to efficiently manage business finances are much better in the cooperative-dominated cluster as compared to the private trader-dominated cluster. Furthermore, the resilience of enterprises during the COVID-19 pandemic was much higher in the cooperative-dominated business environment. Enterprises using more unpaid female household labour were more resilient than others during the pandemic.s